Parametric X-rays generated by electrons in multilayer mirrors mounted inside a betatron; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 267, iss. 5 - Kaplin V. V. Valery Viktorovich; Uglov S. R. Sergey Romanovich; Sohoreva V.V.; Bulaev O. F.; Voronin A. A.; Piestrup M.; Gary C.; Fuller M. (2009, 2009)
Title screen